Evaluation of fermented plant extracts as bioinsecticides in controlling Phenacoccus solenopsis colonies on Hibiscus rosa-sinensis under laboratory conditions - Ahmmed, Sultan; Lau, Wei Hong; Khadem, Ahad Gul; Adam, Nur Azura; Sinniah, Uma Rani (Universiti Putra Malaysia, 2024)
The mealybug, Phenacoccus solenopsis, is a serious pest of Hibiscus rosa-sinensis. The waxy coating on its body may hinder pesticide penetration, and the extensive use of pesticides is risky to humans and the environment. Considering these drawbacks, fermented plant extracts (FPEs) were explored for their potential use in controlling this pest in a more user and environmentally-friendly manner. FPEs derived from eleven plant materials were evaluated against P. solenopsis for their insecticidal activity, mealybug wax removal potential and phytotoxicity effect on H. rosa-sinensis. Five concentrations of FPE [5, 10, 15, 20, and 25% (w/v)] were prepared. Among the 11 FPEs, FPE derived from ficus, kaffir lime, and turmeric were effective in suppressing P. solenopsis with lethal concentration at 50% (LC50 value) less than 20% concentration. Although ficus FPE was the top performer in the insecticidal assay, it induced medium to very high levels of leaf damage after being treated with 15–25% concentration at 24 and 72 hr post-treatment. A low level of leaf damage was observed in treatment with turmeric and kaffir lime FPEs at 72 hr post-treatment. FPEs could remove wax from the body of P. solenopsis with no significant difference among them. In conclusion, the FPE of ficus, kaffir lime, and turmeric showed promising insecticidal effects against P. solenopsis.